[Franklin Search Party, Schwatka] - Klutschak, Heinrich (New York : American Geographical Society of New York; N.Y. : Julius Bien Photo. Lith, 1880)
Maps accompany article pages 237-274 from Journal of the American Geographical Society of New York, vol. XII 1880: "Arctic meeting at Chickering Hall, October 28th, 1880. Reception of Lieut. Frederick Schwatka and his associates of the Franklin Search Party of 1878, 1879 and 1880. Addresses by Chief-Justice Daly, Lieut. Frederick Schwatka, U.S. Army and Dr. Isaac I. Hayes."; "Journal - American Geographical Society, 1880 Vol. XII" -- upper margin.; Removed from (AGS) (PUB) G3 .A5 v.12 1880 Grayscale;